The photography in Rio 2016 Olympic Games: Social media, memes and engagement - Américo, Marcos [UNESP]; Margadona, Laís Akemi [UNESP] (Universidade Estadual de Londrina, 2017)
This paper discusses the photographic production related to the public of the Rio 2016 Olympic Games, and it also includes a brief debate about the manipulation of official photographs in memes. We propose that social media photography was a significant tool to mobilize and approach the event to the universe of the Brazilian spectator, as well as an important media of extension of the Olympic narrative in the transmedia context.
A fotografia dos Jogos Olímpicos Rio 2016: Mídias sociais, memes e engajamento
Keywords: Media ecology; Olympic games; Photography; Social media